Analisis Yuridis Prinsip Single Economic Entity dalam Notifikasi Akuisisi Saham PT Tamaris Hidro - Surahman Surahman; Dhaifa Nisrina; Marwah M. Idris; M. Jordi Primasakti; Muhammad Ananda; Muhammad Mirza Rohadi; Nurul Zahwany; Ria Wanda Karmelia Noor; Safira Dina Fakhirah; Siskawati Melinda Rifiyanti; Sri Kandy; Tri Aulia Akbar; M. Rezy Abdurrahman (Universitas Veteran Bangun Nusantara, 2025)
Fair business competition is guaranteed in Law Number 5 of 1999, including the obligation to notify mergers or acquisitions. However, the case of PT Tamaris Hidro vs. KPPU highlights the ambiguity in this regulation, especially regarding the application of the Single Economic Entity Doctrine. PT Tamaris Hidro argued that the notification obligation had been fulfilled by PT Patria Bakti Abadi, but the KPPU rejected the claim and imposed a fine of IDR 10 billion. This study uses a normative legal approach to analyze the legal basis in decision Number 4/Pdt.Sus-KPPU/2024/PN.Niaga Jkt Pst. The results of the study show that the KPPU regulation has not accommodated business entities with complex ownership structures. As a result, parent companies are still required to make separate notifications, even though they are in the same business group. The implications of this finding emphasize the need to revise the KPPU regulation to be more adaptive to the dynamics of modern business. This study recommends further research on the application of the Single Economic Entity Doctrine in competition law in Indonesia.